Analisa TATO dan DER Terhadap ROE Pada Perusahaan Sub Sektor Pertambangan yang Terdaftar di BEI - Azwansyah Habibie (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to examine the Total Asset Turnover and Debt to Equity Ratio to Profitability in Manufacturing Companies Listed on the Stock Exchange in the Mining Sector. The population used for this study were all manufacturing companies in the mining sector. The sample used was 42 observations. Hypothesis Test Results Total Asset Turnover (TATO) on Return On Equity (ROE) t-count value 0.246 < 1.68 (t-count) and sig 0.621 > 0.05, then the first hypothesis is rejected and H0 is accepted, it can be concluded that Total Asset Turnover (TATO) has no effect on Return On Equity (ROE) and the hypothesis which states that Total Asset Turnover (TATO) has a positive and significant effect on Return On Equity (ROE) is rejected. Hypothesis Test Results Debt to Equity Ratio (DER) to Return On Equity (ROE). The results of the research above are the t-count value of 3.288 > 1.68 (t-table) and sig 0.002 < 0.05, the second hypothesis is accepted and H0 is rejected, it can be concluded that the Debt to Equity Ratio (DER) has an effect on Return On Equity ( ROE) and the hypothesis which states that the Debt to Equity Ratio (DER) has an effect on Return On Equity (ROE) is accepted